Green electronics design and manufacturing : implementing lead-free and RoHS-compliant global products - Shina, Sammy G. (McGraw-Hill's AccessEngineering., 2008)
This state-of-the-art resource brings together contributions by a team of experts from the total electronics supply chain who show how to master the strategy, design, test and implementation issues of meeting global environmental regulations. Edited by the founder of the New England Lead-Free Consortium and filled with over 130 detailed illustrations, "Green Electronics Design and Manufacturing" features: a- Guidance for lead-free conversions while maintaining quality and reliability for printed circuit board production and rework of surface mount technology and palted through holes; b- Restriction of hazardous substances (RoHS) compliance for hex-chrome and future halogen free issues c- Detailed coverage of global environmental regulations and their impact on manufacturing and design processes; d- Techniques for managing corporate strategy and project design teams for green products; e- Proven methods for testing and analyzing green products; f- Proven methods for dealing with the adverse results of green production such as tin whiskers and finish interactions.